2023
DOI: 10.32604/or.2022.028193
|View full text |Cite
|
Sign up to set email alerts
|

Identification and verification of aging-related lncRNAs for prognosis prediction and immune microenvironment in patients with head and neck squamous carcinoma

Abstract: Aging is highly associated with tumor formation and progression. However, little research has explored the association of aging-related lncRNAs (ARLs) with the prognosis and tumor immune microenvironment (TIME) of head and neck squamous cell carcinoma (HNSCC). RNA sequences and clinicopathological data of HNSCC patients and normal subjects were downloaded from The Cancer Genome Atlas. In the training group, we used Pearson correlation, univariate Cox regression, least absolute shrinkage/selection operator regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…In terms of mechanism, TRIM35 expression leaded to the degradation of CLOCK protein, promoting NK cell infiltration in diffuse large B-cell lymphoma [47,48]. Aging could affect immunity, including NK cell function [49,50]. A study reported that long-term shift work would facilitate lung metastasis of B16F10 melanomas by promoting NK cell aging [51].…”
Section: Immune Cells In Tmementioning
confidence: 99%
“…In terms of mechanism, TRIM35 expression leaded to the degradation of CLOCK protein, promoting NK cell infiltration in diffuse large B-cell lymphoma [47,48]. Aging could affect immunity, including NK cell function [49,50]. A study reported that long-term shift work would facilitate lung metastasis of B16F10 melanomas by promoting NK cell aging [51].…”
Section: Immune Cells In Tmementioning
confidence: 99%
“…Additionally, a growing number of data sugguest that autophagy in cancer cells is regulated by long-chain non-coding RNA (lncRNA) [ 14 ]. With a length of over 200 bp [ 15 ], lncRNA has been verified to have extensive impacts on a variety of crucial biological processes, like cell differentiation, proliferation, RNA attenuation, RNA splicing, genetic regulation of gene expression, protein folding as well as microRNA (miRNA) regulation [ 16 19 ]. Reportedly, lncRNA HULC induces liver cancer by suppressing PTEN through autophagy cooperation with miR15a [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%